Contribution of phosphate-solubilizing bacteria in phosphorus bioavailability and growth enhancement of aerobic rice - Panhwar, Q. A.; Radziah, O.; Zaharah Rahman, A.; Sariah, M.; Mohd Razi, I.; Naher, U. A. (Spanish Journal of Agricultural Research, 2011)
The phosphate-solubilizing bacteria (PSB) can solubilize insoluble forms of phosphorous (P) into simple soluble forms that can be taken up by plants. The main focus of this study was to determine the effect of PSB on P availability in presence of different P rates for improved and sustainable rice (Oryza sativa L.) production under aerobic conditions. Triple superphosphate (TSP) at three levels (0, 30 and 60 kg ha–1) and two isolated PSB (Bacillus sp.) strains (PSB9 and PSB16) were tested in glasshouse conditions. Surface sterilized seeds of aerobic rice (M9 variety) were planted in plastic pots containing 3 kg of soil for 60 days. PSB strains exhibited capability of producing organic acids from soil and plant roots and increased yield of aerobic rice. Significantly, high P solubilization (28.7 mg kg–1) and plant uptake (7.94 mg kg–1) was found in PSB16 inoculated treatments at 30 kg ha–1 of P2O5. In this treatment were also observed high leaf chlorophyll content (34.57), photosynthesis rate (7.59 μmol CO2 m–2 s–1) and root development. Isolated strains showed potential to make higher availability of P and increase content of organic acids from soil and roots at lower doses of TSP in aerobic rice. With the production of organic acids (oxalic, malic, succinic and propionic) higher amounts of P in the soil solution increased plant P uptake and resulted in higher plant biomass. The application of these potential inoculants in an appropriate combination with chemical fertilizers could be considered in organic and sustainable aerobic rice cultivation system.